Knowledge about the use of potentially dangerous drugs among hospital health care nurses - Gilvan Oliveira dos Santos; Anny Giselly Milhome da Costa Farre; Ingrede Tatiane Serafim Santana; Hertaline Menezes do Nascimento Rocha; Adriana Andrade Carvalho; Gleyce Kelly de Brito Brasileiro Santos; Ana Liz Pereira de Matos (Universidade Federal do Ceará, 2020)
Objective: to characterize the knowledge about the use of potentially dangerous drugs among hospital health care nurses. Methods: quantitative, descriptive-exploratory research, with the application of a validated questionnaire, translated and adapted in Brazil, on potentially dangerous medications, with 26 nursing assistants from a university hospital. Univariate and bivariate descriptive statistical analysis of the data was performed using the Statistical Package for Social Science, version 20. Scores ≥70% were considered as sufficient knowledge and insufficient knowledge scores <70%. Results: in the first domain of the questionnaire, called Medication Administration, the average percentage of correct answers was 64.6%. In the second domain, Clinical procedures, an average of 53.7% of correct answers was found. The use of electrolytes, chemotherapy and insulin were the main weaknesses in the knowledge of professionals. Conclusion: insufficient knowledge about the administration and clinical procedures of potentially dangerous drugs was identified among hospital care nurses in this scenario.